Pertumbuhan Aset, Capital Expenditure dan Struktur Aset Serta Pengaruhnya Terhadap Kinerja Aset BUMN - Rachmawati, Desiana; Fauziah, Rischa Inung; Wicaksana, Fandi Galang (JURNAL ILMIAH EDUNOMIKA, 2025)
BUMN as a state-owned company is required to be managed transparently and responsibly, including in the utilization of assets. Furthermore, this study aims to provide a comprehensive understanding of the determinants of increasing BUMN asset performance with a focus on asset growth, capital expenditure and asset structure. Quantitative methods were determined to process data and analysis using the SEM-PLS model. The predictor variables used are asset growth (AGR), capital expenditure (CAPEX) and asset structure (STRA) with the dependent variable being asset performance (APERF). Secondary data is used in the form of audited financial reports and annual reports from 27 BUMN for the period 2022 to 2024. The research results show that AGR has a positive and significant influence on APERF, while CAPEX and STRA do not have a significant influence on APERF. The more the company's AGR increases, the better the APERF will be. Effectively managed AGR will encourage efficient use of resources, strengthen financial conditions and create greater added value. Meanwhile, CAPEX cannot directly determine the level of effectiveness of asset performance as a whole. STRA is not a key factor in increasing APERF, but only acts as a component that must be supported by the company's managerial capacity and operational strategy. Keyword: BUMN, asset growth, asset performance, asset structure, capital expenditure